Impact Of Noise And Hearing On Task And Academic Performance Of Primary School Children In Kuala Lumpur - Chua, Swee Kim (2001)
Noise poses a serious threat to children's hearing, health, learning and behavior. This study was done to determine the effects of noise and hearing on task and academic performance of primary school children in Kuala Lumpur. A total of 110 Standard One Malay children aged from 6 1/2 to 7 1/2 years were recruited in this study according to stratified random sampling. Environmental noise levels and personal noise exposures were measured by using sound level meter and noise dosimeter, respectively. A personal questionnaire and audiometric tests was administered on all the respondents. Seven tests in the McCarthy Scales of Children's Abilities constituted the tests in the Task Performance. Task Performance was carried out twice on the same respondents in quiet and noise condition. The child's academic performance was determined by his latest examination result in the school. Environmental noise measurement indicated that a mean equivalent continuous sound level (LEQ), maximum level (LMAX) and minimum level (LMIN) of at least 60 dB (A) was found inside and outside the classrooms irrespective of school days or holidays.